Richard L. Strout papers - Strout, Richard L. (Richard Lee), 1898-
Correspondence, diaries, speeches, writings, notes, research material, military records, financial records, awards, and other papers relating chiefly to Strout's association as a journalist with the Christian Science Monitor, the New Republic, and other publications. Includes Strout (Stroud) family correspondence and diaries recording Strout's trips to England, Ireland, and Scotland in the early 1920s. Correspondents include James MacGregor Burns, Saville R. Davis, William H. Stringer, and E. B. White.
Journalist; died 1990.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Burns, James MacGregor -- Correspondence; Davis, Saville R. -- Correspondence; Stringer, William H. -- Correspondence; White, E. B. -- 1899-1985 -- Correspondence; Stroud family -- Correspondence; Christian science monitor; New republic; American periodicals; Great Britain -- Description and travel; Ireland -- Description and travel; Journalists